Weed management for landscape scale restoration of global temperate grasslands. (30th November 2020) - Humphries, Talia; Florentine, Singarayer K.; Dowling, Kim; Turville, Chris; Sinclair, Steve
Abstract: Globally, temperate grasslands have been significantly degraded as a result of urbanisation, grazing and agriculture. Weeds now dominate most of these ecosystems, resulting in the loss of ecosystem services, reduced carrying capacity for farmers, and reduction of habitat for native plants and animals. This paper reviews the literature relating to temperate grassland restoration efforts across the globe, noting which techniques and combinations have been used successfully to reduce weed dominance and promote native recruitment and establishment. This review concludes that, using a combination of four restoration techniques, provided the highest level of success, with the caveat that, ongoing weed management should be budgeted for in all projects. There is no single optimal method for restoration and weed control, with success depending on specific site conditions and the scope and aims of particular projects. However, any form of target plant transfer was observed to significantly enhance the restoration's success and reduce exotic plant biomass. There is clearly a need for an increase in long‐term monitoring of restoration projects in order to make more confident assumptions.